2016
DOI: 10.1002/joc.4828
|View full text |Cite
|
Sign up to set email alerts
|

The Andes Cordillera. Part II: Rio Olivares Basin snow conditions (1979–2014), central Chile

Abstract: Snow cover extent, duration, and properties were simulated (1979/1980–2013/2014) for the Rio Olivares Basin (548 km2) in central Chilean Andes, in an effort to understand conditions and trends (linear) at a basin scale. The National Aeronautics and Space Administration Modern‐Era Retrospective Analysis for Research and Applications products, together with the snow modelling software package SnowModel allowed simulations of first‐order atmospheric forcings (mean annual air temperature (MAAT) and water‐equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 64 publications
(111 reference statements)
1
23
1
Order By: Relevance
“…An increase in air temperature, for example, causes the 0°C isotherm to ascend to higher elevations resulting in a larger proportion of precipitation falling as rain as opposed to snow. Mernild et al (2016c) observed this phenomenon for the Olivares basin (33°12' S; 70°09' W) between 1979 and 2014, where precipitation has been increasingly falling as rain in recent years. This change in the partitioning of precipitation over mountainous areas can offset the positive effects of increased precipitation on snow accumulation, with rainfall often enhancing snow and ice melt rates on glacier surfaces.…”
Section: Drivers Of Change On Snow Cover Variablesmentioning
confidence: 82%
See 4 more Smart Citations
“…An increase in air temperature, for example, causes the 0°C isotherm to ascend to higher elevations resulting in a larger proportion of precipitation falling as rain as opposed to snow. Mernild et al (2016c) observed this phenomenon for the Olivares basin (33°12' S; 70°09' W) between 1979 and 2014, where precipitation has been increasingly falling as rain in recent years. This change in the partitioning of precipitation over mountainous areas can offset the positive effects of increased precipitation on snow accumulation, with rainfall often enhancing snow and ice melt rates on glacier surfaces.…”
Section: Drivers Of Change On Snow Cover Variablesmentioning
confidence: 82%
“…The 0°Cisotherm for the western side of the cordillera (40 km northeast of Santiago de Chile), was located at 3,385 m a.s.l. between 2009 and 2014 (Mernild et al 2016c).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations